(untitled) (Iranian Journal of Kidney Diseases, 2012)
Herbal medicines are being used with greater frequency by practitioners of natural medicine in the United States. Many categories of herbs are used, primarily angiotensin antagonists, nonspecific nephroprotective, and immunomodulating/adaptogenic herbs. The most common herbs in each category are discussed both from a historical and scientific perspective. For the first time, a case series of the use of the proposed herbal angiotensin antagonist herb indigenous to the United States, Lespedeza capitata, is reported based on the author’s clinical practice.